Experimental studies of the grinding process by planetary grinding head - Kalinichenko, Nikolai (Technology audit and production reserves, 2018)
The object of research is the process of creep feed grinding of parts of aircraft engines with hard-to-machine materials. In the aviation industry from such materials (steel 4Х5МФ1С, ХН53КВМТЮБ, etc.) blades and disks of turbines, segments of nozzle apparatuses, sectors of input guide vanes, plungers, pistons, gears, etc. similar details are made. Blade processing methods are not very effective in creating such parts. Increased wear of technological equipment and tools leads to an increase in temperature in the cutting zone, adversely affects the quality indicators and reduces the life of the product as a whole. Constant sharpening, editing or changing the tool to a new, additional adjustment of the process equipment leads to an increase in the cost of manufacturing parts from difficult-to-work materials. The introduction of creep feed grinding in technological processes allows to avoid the above negative factors. The increase in the technological modes of grinding reduces the processing time, but it becomes a cause of burn in the surface layers and damage to the processed surface. Experimental studies of the process of creep feed grinding are carried out to determine the temperatures in the subsurface layers of the part during its processing and subsequent comparison with the theoretically obtained results of the developed mathematical model. Processing was performed on a surface grinding machine Jotes SPD-30b (Poland). The temperature is measured by the contact method (measuring instrument ОВЕН МВА 8, Russia) and contactless (using a pyrometer СТ 3M, Germany). The results of the experimental temperature values are given in tabular form. According to the research results, it is found that the use of a planetary grinding head for the technology of creep feed grinding of machine-building and aviation parts of difficult-to-process, corrosion-resistant materials leads to a decrease in the power-process parameters. In addition, there is an improvement in the surface cleanliness class (surface roughness Ra is between 1.25-1.8 μm). The results suggest that the technology of creep feed grinding should be introduced into technological processes instead of milling, external pulling and traditional grinding.